1996
DOI: 10.1121/1.414729
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new standard laboratory protocol for estimating the field attenuation of hearing protection devices. Part I. Research of Working Group 11, Accredited Standards Committee S12, Noise

Abstract: This paper describes research conducted by Working Group 11 of Accredited Standards Committee S12, Noise, to develop procedures to estimate the field performance of hearing protection devices ͑HPDs͒. Current standardized test methods overestimate the attenuation achieved by workers in everyday use on the job. The goal was to approximate the amount of attenuation that can be achieved by noise-exposed populations in well-managed real-world hearing conservation programs, while maintaining acceptable interlaborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…Training is critical for HPD users (Berger, 2000;Royster et al, 1996); however, few studies have been conducted on inexperienced HPD users and individuals from non-occupational populations. Newly hired industrial employees frequently are required to attend safety indoctrination training that lacks recommended hearing loss prevention training components.…”
Section: Sumariomentioning
confidence: 99%
See 1 more Smart Citation
“…Training is critical for HPD users (Berger, 2000;Royster et al, 1996); however, few studies have been conducted on inexperienced HPD users and individuals from non-occupational populations. Newly hired industrial employees frequently are required to attend safety indoctrination training that lacks recommended hearing loss prevention training components.…”
Section: Sumariomentioning
confidence: 99%
“…A pair of new earplugs in unopened packages was positioned in front of each participant. The experimenter did not provide assistance or training at the time that the subject was told to insert the hearing protectors (Franks et al, 2000;Royster et al, 1996). Also, no commentary or feedback was available during the fitting, including any suggestions to use the manufacturer's directions placed in front of the subject or on the product packet.…”
Section: Pre-trainingmentioning
confidence: 99%
“…If one were observing or training a shooter at a firing range, peak impulse levels could easily exceed 140 dB and hearing protection should always be worn. Poorly fit protectors have low REAT attenuations and may provide only a few decibels of protection against high-level impulses (Royster et al, 1996;Murphy & Tubbs, 2007;Murphy et al, 2009). Berger and Hamery (2008) demonstrated that several earplugs provided a small amount of protection.…”
Section: Implications For Rating Performancementioning
confidence: 99%
“…The laboratory-based attenuation values used in the following analyses are the average of each test subjects' two trials in the Subject-Fit 1 test session, and their two trials in the Subject-Fit 2 test session, from the interlaboratory study as reported in Table II of Royster et al ͑1996͒. This provided a single attenuation value for each of 24 subjects at each of four laboratories, based on four attenuation measurements per subject.…”
Section: A the Laboratory Data Samplementioning
confidence: 99%
“…II C and Fig. 1 of Royster et al ͑1996͒. They include the Aearo Company E-A-R ® Classic foam earplug, the PlasMed, Inc. V-51R premolded earplugs ͑5 sizes͒, the Willson Safety Products EP100 premolded earplugs ͑2 sizes͒, and the Bilsom UF-1 earmuffs.…”
Section: A the Laboratory Data Samplementioning
confidence: 99%